Effect of the Dielectric Barrier Discharge Plasma on the Optical Properties of CDS Thin Film (Baghdad Science Journal, 2019)
Cadmium sulphide CdS films with 200 nm have been prepared by thermal evaporation technique on glass substrate at substrate room temperature under vacuum of 10-5mbar.In this paper, the effect of Dielectric Barrier Discharge plasma on the optical properties of the CdS film. The prepared films were exposed to different time intervals (0, 3, 5, 8) min. For every sample, the Absorption A, absorption coefficient α , energy gap Eg ,extinction coefficient K and dielectric constant ε were studied. It is found that the energy gap were decreased with exposure time, and absorption , Absorption coefficient, refractive index, extinction coefficient, dielectric constant increased with time of exposure to the plasma. Our study considers the first investigation of the effect of cold atmospheric plasma on the optical properties of CdS film.